PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI DALAM PEMBELAJARAN IPAS PADA MATERI MENJADI PAHLAWAN LINGKUNGAN KELAS IV SEKOLAH DASAR - Nur Anisah Nasution; Aprilia, Rapita; Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by issues in Natural and Social Sciences (IPAS) learning in Class IV at SDN 10 Langsa. Educators still predominantly rely on textbooks as the main learning source, causing students to tend to lose focus during the learning process. Therefore, this study aims to develop a learning medium tailored to students' needs, test the feasibility, and ensure the practicality of an animated video learning medium based on Canva and CapCut applications covering the topic